Preliminary Study of NFRP-Confined Concrete for Enhancing Compressive Strength - Taufiq Saidi; Muttaqin Hasan; Zahra Amalia (Aceh International Journal of Science and Technology, 2023)
Earthquake that occurred within a period of several years may be caused reinforced concrete column fails to maintain its performance. Reinforcement methods to improve the quality of concrete in resisting earthquake loads are needed. Strengthening the column with external restraints is expected to increase the strength of the concrete. The use of synthetic Fiber Reinforced Polymer (FRP) as a composite material for external restraint on structures is one of the materials that has been widely used for strengthening concrete structures. Considering the environmental impact, natural FRP materials have been developing nowadays. One of the natural fibers that have been researched and used as a composite material for Natural Fiber Reinforced Polymer (NFRP) is abaca fiber. This research aims to find the contribution of abaca fiber in increasing the compressive strength of confined concrete as a preliminary study. In this study, the test was carried out by applying a compressive load to concrete specimens reinforced with NFRP restraints. The NFRP was investigated with variations in the number of NFRP layers. The results showed that NFRP-confined concrete has a higher compressive strength of 34.73% than the controlled specimen